Project Duration Performance Measurement By Fuzzy Approach under Uncertainty (European Journal of Pure and Applied Mathematics, 2017)
In recent years, a various of novel techniques for measuring project performance have been proposed. The Earned Duration Management (EDM) is the most recent technique which uses time-based data exclusively. In this paper, as the uncertainty is inherent in real-life activities, linguistic terms are used to describe progress of activities rather to evaluate it deterministically and a fuzzy approach is applied on EDM methodology. The proposed approach derived development of new fuzzy indices which are capable of measuring project duration performance under uncertainty. A small example illustrates how the proposed model can be employed in reality.